Developing an Extended IFC Data Schema and Mesh Generation Framework for Finite Element Modeling. (3rd October 2019) - Xu, Zhao; Rao, Zezhi; Gan, Vincent J. L.; Ding, Youliang; Wan, Chunfeng; Liu, Xinran
Abstract : Mesh generation plays an important role in determining the result quality of finite element modeling and structural analysis. Building information modeling provides the geometry and semantic information of a building, which can be utilized to support an efficient mesh generation. In this paper, a method based on BRep entity transformation is proposed to realize the finite element analysis using the geometric model in the IFC standard. The h-p version of the finite element analysis method can effectively deal with the refined expression of the model of bending complex components. By meshing the connection model, it is suggested to adopt the method of scanning to generate hexahedron, which improves the geometric adaptability of the mesh model and the quality and efficiency of mesh generation. Based on the extension and expression of IFC information, the effective finite element structure information is extracted and extended into the IFC standard mode. The information is analyzed, and finally the visualization of finite element analysis in the building model can be realized.